TRANSFORMING HEALTHCARE THROUGH UNIFIED COMMUNICATIONS: INTEGRATION, COMPLIANCE, AND PATIENT CARE EXCELLENCE - Naga Praneeth Yerram, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This comprehensive article analysis explores the transformative impact of Unified Communications (UC) in healthcare settings, focusing on integration, compliance, and patient care excellence. The article examines how UC systems have revolutionized healthcare delivery through advanced communication channels, patient-centric solutions, and robust security frameworks. The article investigates the core components of healthcare UC systems, including VoIP integration, video conferencing capabilities, and secure messaging platforms, while analyzing their collective impact on healthcare delivery efficiency. The article delves into patient-centric communication solutions, emphasizing telehealth implementation and accessibility features that have enhanced healthcare access across diverse populations. Furthermore, it examines regulatory compliance and security measures essential for protecting patient information while maintaining operational efficiency. The article also evaluates the implementation benefits across clinical and operational domains, highlighting patient outcomes, team collaboration, and resource utilization improvements. Finally, it explores future trends and developments, including artificial intelligence integration, IoT device connectivity, and emerging communication technologies that promise to revolutionize healthcare delivery further.